New insights into the mechanism of rehydration of milk protein concentrate powders determined by Broadband Acoustic Resonance Dissolution Spectroscopy (BARDS). (December 2016) - Vos, Bastiaan; Crowley, Shane V.; O'Sullivan, Jonathan; Evans-Hurson, Rachel; McSweeney, Seán; Krüse, Jacob; Rizwan Ahmed, M.; Fitzpatrick, Dara; O'Mahony, James A.
Abstract: This study investigated the transfer of water into milk protein concentrate (MPC) powder particles using Broadband Acoustic Resonance Dissolution Spectroscopy (BARDS) as a detection method for the first time. BARDS analysis is based on an acoustic phenomenon which occurs during powder rehydration. Release of air from the powder into the solvent during rehydration leads to outgassing in the solvent, which results in changes in solvent compressibility that are monitored through accompanying changes in induced resonance frequencies in the dissolution vessel. BARDS confirmed that water transfer into MPC particles became increasingly inhibited as protein content of the powder increased. The reproducibility of the data indicates that air release from internal vacuoles within powder particles in high-protein MPCs is a highly ordered process, occurring over a protracted time scale. Kinetic modelling of gas volume data from BARDS confirmed that the release of occluded air caused the changes in solvent compressibility during rehydration. The physicochemical properties of solubilised protein had a slight inhibitory effect on escape of bubbles from the solvent, but the primary factor limiting gas release from high-protein MPCs was water transfer into powder particles and the concomitant release of occluded air into the solvent. In agreement with many previous studies, cryo-SEM analysis showed that particles in high-protein MPCs were slow to disperse; the current study, in addition, highlights inhibited water transfer into particles as another factor which may contribute to their poor rehydration properties. A potential link between inhibited water transfer and poor dispersibility is proposed. Graphical abstract: